MARKETING STRATEGY FOR LIBRARY SERVICES IN THE ERA OF DIGITAL TECHNOLOGY - Putri, Bella Bintari; Miranda, Mika Nofaj; Suniati, Rita; Maimanah, Venni (Academic Solution Publisher, 2023)
The purpose of writing this article is to understand the concept of marketing library services in the era of digital technology. Marketing, in general, is closely related to real products and is profit oriented. Marketing is not limited to the business world, but is also important for non-profit oriented institutions, agencies or organizations, including libraries. Marketing in libraries does not market goods products, but library service products for the benefit of library users. In order for the library to be optimal in its services for library users, it needs certain tips related to marketing library services. In this way, the forms of services and service tasks provided can be well organized.